How persistent low expected returns alter optimal life cycle saving, investment, and retirement behavior - Vanya Horneff; Raimond Maurer; Olivia S. Mitchell (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This Chapter explores how an environment of persistent low returns influences saving, investing, and retirement behaviors, as compared to what in the past had been thought of as more "normal" financial conditions. Our calibrated lifecycle dynamic model with realistic tax, minimum distribution, and Social Security benefit rules produces results that agree with observed saving, work, and claiming age behavior of U.S. households. In particular, our model generates a large peak at the earliest claiming age at 62, as in the data. Also in line with the evidence, our baseline results show a smaller second peak at the (system-defined) Full Retirement Age of 66. In the context of a zero-return environment, we show that workers will optimally devote more of their savings to non-retirement accounts and less to 401(k) accounts, since the relative appeal of investing in taxable versus tax-qualified retirement accounts is lower in a low return setting. Finally, we show that people claim Social Security benefits later in a low interest rate environment.
urn:nbn:de:hebis:30:3-451952
Keywords: G11; G22; D14; D91; 330; dynamic portfolio choice; 401(k) plan; saving; Social Security claiming age; retirement income; minimum distribution requirements; tax